KETERSEDIAAN INFRASTRUKTUR DASAR DAN PERENCANAAN TATA RUANG KECAMATAN SAMARINDA UTARA - Akhmad Yani (Bajang Institute, 2026)
Basic infrastructure plays a pivotal role in shaping urban spatial structures and sustaining service systems within cities. Rapid population growth and ongoing development in North Samarinda District have intensified demands for housing facilities, clean water supply, and solid waste management. This study aims to identify the availability and assess the requirements of basic infrastructure through spatial analysis, demographic evaluation, and reference to established policy standards in spatial planning. The findings reveal that most sub-districts require additional housing facilities, improvements in clean water provision, and enhanced waste management infrastructure. In contrast, Sempaja Selatan and Sempaja Timur sub-districts demonstrate relatively adequate provision of basic infrastructure compared to other areas.